Disaster Resilient Cities in Nepal: Disaster Management Efforts of Biratnagar Metropolitan City - Upadhyay, Chandra (Journal of Research and Development, 2023)
Disaster resilient, safe, inclusive and sustainable space is required for all. But Nepal is facing challenges due to inadequate disaster response. The primary objective of this study is to assess the local government’s preparedness and efforts in management of human shelters and public occupancy, in addition to prompt response, rescue and rehabilitation mechanisms as well as supply management to any disaster affected population in the city. Taking Biratnagar Metropolitan City of Koshi Province as a case, this study answers the question of what disaster challenges exist in the city and how the local government responded to those situations and why the responses were not adequate. The present research uses both primary and secondary data to make an assessment of the status, preparedness, actions and challenges of the city governance of Biratnagar Metropolitan City in management of disaster safety and people’s awareness building on safe city issues which significantly aids in bringing disaster management in the city. The findings indicate that the emphasis on early preparedness and sustainable initiatives on disaster management remained in the marginal reference of the local level disaster planning. The local government’s focus is found generally active in rescue and relief during disasters when a paradigm shift through early preparedness has become a core area of concern in disaster management for a sustainable development globally. This paper is believed to draw attention of the policy makers at the local level and lead the discourse further for the academicians.